Media Studies: A Reader - Sue Thornham; Caroline Bassett; Paul Marris (New York New York University Press, 2009)
Media Studies: A Reader introduces a full range of theoretical perspectives through which the media may be explored, analyzed, critiqued, and understood. Media Studies: A Reader includes essential essays from writers such as Raymond Williams, Stuart Hall, Marshall McLuhan, Jurgen Habermas, Jean Baudrillard, and Michel Foucault, whose work was central to forming the field. It also includes wide ranging work on current media formations from key contemporary theorists, including Paul Gilroy, Angela McRobbie, and Nick Couldry. Finally, Media Studies: A Reader looks to the future, exploring new media formations and their significance through the work of Mark Andrejevic, Lev Manovitch, Jonathan Sterne, Janice Radway, Ien Ang, David Morley, Linda Williams, and others. The sixty-seven readings are divided into two main parts. "Studying the Media" begins with a section on key theoretical perspectives and follows this with five sections opening up questions around the Public Sphere, Representation, Feminism and Gender, Audiences, and Everyday Life. The second part, "Case Studies," brings together concrete examples of how theoretical approaches can be realized through a series of case studies, covering, for instance, reality TV, news, advertising, and new media. With easy-to-follow introductions and guides to further reading accompanying each section, Media Studies: A Reader equips the student to engage with key debates in the field. With over 60% new material, this new edition updates all sections with a rich selection of contemporary writing complementing media studies classics. In addition, further reading lists have been comprehensively updated and introductory essays to each section have been expanded and re-written.
Keywords: Nonfiction; Media; Global Citizenship (BIN1064-N)